EFFECT OF SOURCE AND TIMING OF NITROGEN FERTILIZER ADDITION ON GROWTH AND YIELD OF SUDAN GRASS (Sorghum sudanense L.) - Salim Al-Ghazal; Waleed Al-Juheishy (Mesopotamia Journal of Agriculture)
In the spring of 2022, a field experiment was carried out in two locations: the first was in the village of Al-Thalja, which is located 15 km northwest of the city of Mosul, and the second location was in the village of Al-Shuhada, which is located 30 km west of Mosul. The experiment included two factors, the first two types of nitrogen fertilizer: urea (46%N) and DAP (18%N and 46%P). The second factor included four levels of dividing the two fertilizers: the first level was (half the amount of DAP with planting, the other half after 20 days of planting, and the second was half. The amount of DAP with planting and the other half after 40 days of planting, the third level is half the amount of urea with planting and the other half after 20 days of planting, The fourth level is half the amount of urea with planting and the other half after 40 days of planting). The fertilizer rate used for both types was: 100kg/ha. The experiment was conducted according to a split-plate system with a randomized complete block design (R.C.B.D) with three replications, and the results are summarized as follows: All growth, yield, and qualitative traits of the treatments to which DAP fertilizer was added were superior to those to which urea fertilizer was added in the two study locations. The first fractionation of the DAP fertilizer gave a higher Value for all growth traits, yield, and qualitative traits at the two study locations.